A biomedical educational intervention to change explanatory models of psychosis among community health workers in South India - Joel, D. (Medknow Publications, 2006)
BACKGROUND: Community health workers in developing countries commonly hold indigenous beliefs about mental illness which differ markedly from biomedical models. AIM: To test the effect of a biomedical intervention on explanatory models (EMs) of community health workers. METHODS: Indigenous beliefs about chronic psychosis were elicited from community health workers. The Short Explanatory Model Interview formed the basis of the interview. Half the workers were taught about the biomedical model after discussing their EMs of chronic psychosis. The others did not receive education. The beliefs of all community health workers were reassessed 2 weeks after the initial assessment. RESULTS: A variety of indigenous beliefs, which contradicted the biomedical model, were elicited at the baseline evaluation. Seeking biomedical help at follow up was significantly related to receiving education about the biomedical aspects of chronic psychosis (OR 17.2; 95% CI: 18.75, 15.65; p<0.001). This remained statistically significant (OR 9.7; 95% CI: 82.28, 1.14; p<0.04) after using logistic regression to adjust for baseline variables. CONCLUSION: The high prevalence of non-medical beliefs among community health workers suggests the need to elicit and discuss beliefs before imparting knowledge about biomedical models of mental disorders. Biomedical educational intervention can change EMs of mental illness among health workers.